The Essence of the Teaching of Causality in Revealing Deaths Due to Premeditated Murder - Budiyanto, Budiyanto; Pamolango, Valentino; Ringgi, Deppa (Faculty of Law, Universitas Pattimura, 2024)
Introduction: This article analyzes the contribution of the doctrine of causality in uncovering deaths resulting from premeditated murder. The doctrine of causality is essentially very important and needed to determine a person's guilt for actions that cause consequences. It is appropriate for the defendant to be processed, prosecuted and sentenced to life imprisonment according to the level of guilt.Purposes of the Research: The aim of this research is to examine more specifically the importance of the doctrine of causality in uncovering someone's death as a result of premeditated murder in Jayapura City and the obstacles.Methods of the Research: The method chosen is normative legal research with an emphasis on secondary data. The statutory approach and case approach were chosen to study the application of the doctrine of causality. So that it can be known with certainty the determination of guilt and criminal responsibility. Primary legal materials and secondary legal materials are sources of data collection. Analysis of research results is carried out by providing criticism, support, comments, then a conclusion is made using a literature review.Results of the Research: The research results prove that in uncovering the case of the death of a victim of premeditated murder in Jayapura City, law enforcement officers chose a generalizing theory. In an effort to search for and find the relationship between the defendants' actions, the combined balance theory becomes the starting point for determining the defendant's guilt. The combined balance theory has the advantage that it can be used to calculate carefully and precisely. Both defendants were sentenced to life imprisonment for the crimes they committed. The obstacle is the difficulty of finding witnesses, evidence and other evidence.